PENGARUH KOMPENSASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS SOSIAL KABUPATEN NIAS SELATAN - Christian F.S. Wau (Universitas Nias Raya, 2023)
This study aims to determine the effect of compensation for employee performance at the South Nias District Social service office. Causal quantitative research types. The population in this study amounted to 32 Non civil servants. The type of data in this study is to use primary data. The data analysis used is simple linear regression . The result of this study indicate that compensation affects the performance employees. Furthermore in this study it was obtained a simple linear equation is: 28,101 + 0,394X which means that the value (α) is a big 28,101 as the value of (b) is 0,394. The coefficient of determination () 0,989 (98,9%) so that it can be shown that the 98,9 diversity of bound variables can be explained by independent variables. While the value 1,954 and while value (1,697) with a significant level 0,034 < 0,05. Thus it can be concluded that is rejected and is accepted meaning the compensation variables has a significant influence on employee performance at the South Nias Regency Social service office. Suggestion in this study are: leader need to pay attention to compensation that is fair in accordance wirth the work done, for the next researcher to add other variables from the variables studied so that they can grow broad insights, it this hoped that they can respect time because it is in accordance withb applicable regulations.